PELAKSANAAN PELATIHAN EVAKUASI DALAM SITUASI DARURAT UNTUK MENINGKATKAN KESELAMATAN PENUMPANG KAPAL DI KMP JATRA 2 - eka, yudha (Jurnal Ilmiah Kemaritiman Nusantara, 2024)
The incidence of accidents and occupational diseases is still quite high. Various ship incidents include sinking, collision, fire, aground, people falling overboard, steering damage, and pollution at sea. as well as work accidents during duty on the ship, generally caused by human factors or human error. The purpose of this study is to find out the emergency drills on the ship, based on SOLAS on the KMP Jatra 2 ship and to find out how to handle problems in maximizing job training to each crew member according to SOLAS and SOP regulations. The results of this study found that emergency training on board KMP Jatra 2 is not running properly due to lack of consistency in following the SOP and SOLAS standards that have been set. To deal with this problem, several steps need to be taken, namely good HR policies, implementation of a punishment system for undisciplined crew members, regular training and realistic simulation of emergency situations, continuous supervision and evaluation of training implementation